The Value of Gamification as a tool for capturing student attention: a mixed method study - Barca, Alessandro; Tripaldi, Mariella (European Public & Social Innovation Review, 2024)
Introduction: Gamification, the use of game design elements in non-game contexts, is a valuable tool for enhancing learning, particularly for students with special educational needs (SEN). This study explores its benefits in educational settings and its impact on classroom management. Methodology: The research, involving 200 primary school teachers, employs both quantitative and qualitative methods. The objectives are to gather teachers' perceptions of gamification and to correlate their activities with student evaluations. Results: Findings reveal that teachers require both technological and methodological support to effectively utilize these tools. Gamified activities increased student engagement and motivation, improved classroom management, and strengthened the sense of belonging among students. Discussions: Despite the increased workload for teachers, they consider the benefits for student learning and classroom dynamics to outweigh the challenges, supporting continued use of this strategy. The study highlights the importance of comprehensive support systems for teachers implementing gamification, covering both technical training and pedagogical development. Conclusion: It concludes that gamification is a promising approach for creating inclusive and dynamic educational environments.